Penelitian Perilaku Bullying Berdampak Terhadap Kondisi Psikososial - Shifa Raihana Septiani; Ageng Saepudin Kanda S (Student Scientific Creativity Journal, 2024)
Bullying is a form of violence that occurs in teenagers. Bullying is a form of violent behavior with the power to hurt a person or group verbally, physically or psychologically. The impact that victims of bullying have is having various mental problems and physical health complaints. Therefore, social support from the family is really needed by victims of bullying. This research is a qualitative study which aims to obtain an overview of family social support for adolescent victims of bullying so that they can restore their social functioning and regain trust. himself so that he can carry out his role in society as usual. The data source selection technique used in this research uses Qualitative methods using verbal data obtained by researchers can reveal information in more depth. So, researchers can describe the psychological dynamics of victims of bullying behavior among teenagers at school. Where the approach cannot be expressed by numbers or quantitatively. The research results show that social support has an important role in protecting victims of bullying from psychological and physical illnesses. However, support from the family has several inhibiting factors, including rejection and withdrawal from the victim. Apart from that, family busyness, indifference or ignorance are also factors inhibitor.